2019
DOI: 10.1042/bsr20181367
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lncRNA RMRP ameliorates oxygen-glucose deprivation/re-oxygenation-induced neural cells injury by inhibiting autophagy and PI3K/Akt/mTOR-mediated apoptosis

Abstract: The aberrant expression of lncRNAs has been inferred to be closely related with the progression of neural ischemia/reperfusion (I/R) injury. RMRP is an lncRNA associated with I/R injury. In order to determine the role of RMRP in I/R injury, the effects of RMRP knockdown on oxygen-glucose deprivation/re-oxygenation (OGD/R)-induced injury in SH-SY5Y cells were evaluated. The effect of OGD/R administration on the expression of RMRP and apoptosis in SH-SY5Y cells, and the effect of RMRP suppression by siRNA on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Wang et al suggested that Homer1a relieved neuronal injury induced by traumatic damage by inhibiting PI3K/AKT/mTOR signaling ( Wang et al, 2020 ). PI3K/Akt/mTOR signaling was also involved in oxygen-glucose deprivation/re-oxygenation-induced neuron injury ( Zhou et al, 2019 ). In addition, NF-κB pathway can be activated by Akt protein kinases and involved in various functions, such as immune, inflammation, apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al suggested that Homer1a relieved neuronal injury induced by traumatic damage by inhibiting PI3K/AKT/mTOR signaling ( Wang et al, 2020 ). PI3K/Akt/mTOR signaling was also involved in oxygen-glucose deprivation/re-oxygenation-induced neuron injury ( Zhou et al, 2019 ). In addition, NF-κB pathway can be activated by Akt protein kinases and involved in various functions, such as immune, inflammation, apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicated that the activation of NF-κB signaling pathway was relevant to nerve injury ( Theus et al, 2017 ; Mettang et al, 2018 ). Indeed, it has also been demonstrated that Akt signaling pathway is involved in neuronal injury ( Zhou et al, 2019 ; Wang et al, 2020 ). Phosphorylation of Akt can activate IKKs, leading to phosphorylation and degradation of IKB, p65 nuclear translocation ( Ya et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that MCAO treatment caused noticeably increased infarcted size in mice (Figure 1 It has been reported that RMRP inhibition improves OGD/Rinduced neuron damage, 11 and miR-613 can inhibit I/R-induced cardiomyocyte apoptosis. 16 In addition, ATG3 also plays a role in I/R injury.…”
Section: Lncrna Rmrp and Atg3 Was Significantly Highly Expressed In Mcao Mouse Brainmentioning
confidence: 92%
“…9 The effect of RMRP on the pathogenesis of brain disease has been verified, and RMRP is tightly associated with I/R injury. 10,11 However, the underlying mechanism of RMRP in cerebral I/R injury remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the stress is prolonged or extensive, homeostasis within the cell is disrupted leading to apoptosis, which is primarily mediated by Ca 2+ overload, or autophagy (Berridge et al, 2000 ; Bernales et al, 2006 ; Ding et al, 2007 ; Høyer-Hansen and Jäättelä, 2007 ). Autophagy, e.g., caused by oxygen and glucose deprivation and reoxygenation, may maintain cellular homeostasis, but its excessive level may lead to autophagic neuronal necrosis and apoptosis (Ahsan et al, 2019 ; Zhou et al, 2019 ). Differences in cytosolic Ca 2+ levels associated with autophagy and apoptosis have been demonstrated in several cell lines.…”
Section: Stim Proteins In the Physiology Of Neurons Autophagy And Nmentioning
confidence: 99%